KEARIFAN LOKAL DALAM USAHA TANI UBI JALAR DI KELURAHAN KOYA KECAMATAN TONDANO SELATAN KABUPATEN MINAHASA - Maiter Uaga; Melsje Yellie Memah; Jean Fanny Junita Timban (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine the local wisdom of sweet potato farming in the Koya Village. This research was conducted in Koya Village, South Tondano District, Minahasa Regency. Sampling using a purposive sampling method, deliberately chose farmers who cultivate sweet potatoes as many as 10 people who are local sweet potato farmers. The data collected is primary data and secondary data. Primary data data obtained from interviews with sweet potato farmers with the help of a list of questions. Secondary data were obtained from the Koya Kelurahan government, as well as scientific papers related to research. The results showed that local wisdom in sweet potato farming in Koya Village was in the process of preparing land where farmers could differentiate land based on the color and type of soil so as to produce good sweet potatoes. In tillage, sweet potato farmers provide grain from the remnants of rice so that the soil can be fertile and the sweet potato produced is large and makes it easier to harvest.*eprm*